The Phenomenon of Autocratic Legalism in the Formation of Laws and Regulations in Indonesia - Sania Putri, Salsabella (Realism: Law Review, 2025)
The autocratic phenomenon of legalism in the formation of laws and regulations in Indonesia refers to the use of legal instruments to consolidate authoritarian power through a process that seems legal, but is contrary to democratic principles. This study aims to analyze how this practice occurs in the legislative process, as well as its impact on the Indonesian constitutional system. Through a qualitative approach with literature studies and case analysis. This study found that autocratic legalism is manifested through executive dominance in law-making, weakening of public participation, and the use of law as a tool of repression. Concrete examples include the hasty passage of the Job Creation Law and the revision of the KPK Law that reduces the independence of anti-corruption agencies. As a result, there has been a narrowing of the democratic space, inequality in law enforcement, and a weakening of the legislative oversight function. This study concludes that a more transparent and participatory reform of the legislative process is needed to prevent the degradation of constitutional democracy in Indonesia.